Study of Aqueous Extraction of a New Anti-Inflammatory Agent Based on Aerva Lanata - A. Akhmadkhuzhaeva; Z. N. Eshmuratov; H. M. Kamilov (Scientific Trends, 2025)
Herbal teas in filter bags form a significant segment due to their convenience and safety. Diuretic compositions are in demand for those prone to microlithiasis (the formation of small salt crystals) and recurrent urinary tract inflammation. Pol-pala is traditionally used as a mild diuretic with litholytic and anti-inflammatory effects, while corn silk additionally provides osmotic diuresis. This paper presents experimental results on the development of a filter bag composition for a mixture of the aforementioned medicinal plants. It was found that increasing the temperature and infusion time to 30 minutes and 95-100 ° C significantly increases the extraction of extractive substances, including flavonoids. A method for quantitatively assessing the yield of total flavonoids calculated as rutin is proposed. An acceptable consumer brewing regimen for filter bags is demonstrated: one bag (2.0 g) per 200 ml of water at 95-100 ° C, infuse for 20-30 minutes.
Keywords: Aerva lanata , Stigmata maydis , extraction, filter bags, flavonoids, extractive substances, extracts, spectrophotometry, phytotherapy.